A Study on the Religious Individuals’ Level of Knowledge about Islamic Finance Principles and Islamic Finance Instruments - Özpolat, Ayşe; Taşar, Sezin Açık (Recep Tayyip Erdoğan Üniversitesi, 2024)
Islamic finance includes financial practices and instruments created by Islamic concepts based on faith and moral values. Fear of Allah, as the center of the Islamic faith, is a phenomenon that raises awareness in all areas of life, including financial transactions. The aim of this study is to evaluate the relationship between religious people's fear patterns and their knowledge about Islamic finance principles and instruments. In the study, data was collected through a survey to evaluate the awareness and fear styles of the participants in the sample of religious individuals regarding Islamic financial principles and Islamic financial instruments. In order to measure the variables in the study, the Fear Types Scale, Religiosity Scale, Islamic Financial Instruments Scale, and Islamic Finance Principles Scale were used. According to the findings of the study, a positive, low-level significant relationship was found between the participants' religiosity and the level of knowledge of Islamic financial instruments, and a positive significant relationship was found between the fear of death and the level of knowledge of Islamic financial instruments. Other results show that there were significant positive relationships between the participants' knowledge of Islamic financial instruments and the variables of gender, age, occupation, and income status.

İslami finans, temelleri inanç ve ahlaki değerlere dayanan İslami kavramların oluşturduğu finansal uygulamaları ve ürünleri içerir. Allah korkusu İslami inancın merkezi olarak finansal işlemler de dahil olmak üzere hayatın her alanında farkındalık yaratan bir olgudur. Bu çalışmanın amacı dindar insanların korku kalıpları ile İslami finans ilkeleri ve ürünleri hakkındaki bilgileri arasındaki ilişkiyi değerlendirmektir. Çalışmada dindar bireylerin oluşturduğu örneklemde yer alan katılımcıların İslami finansal prensiplere, İslami finansal ürünlere ilişkin farkındalığını ve korku biçimlerini değerlendirmek için anket yoluyla veri toplanmıştır. Çalışmada değişkenleri ölçebilmek için korku biçimlerine ait sorular, dindarlık değişkenini ölçen sorular, “İslami Finans Ürünleri Ölçeği”, “İslami Finans Prensipleri Ölçeği” kullanılmıştır. Levene testinin sonuçlarına göre bağımsız değişkenlere analiz yapılmıştır. Çalışmada elde edilen bulgulara göre, İslami finans ürünleri bilgi düzeyiyle katılımcıların dindarlıkları, ölüm korkusu, cinsiyet, yaş, meslek ve gelir durumu değişkenleri arasında pozitif anlamlı bir ilişki bulunmuştur. Yapılan Cohen’s ve Eta kare analizlerine göre ise cinsiyet ile İslami finans ürünleri bilgi düzeyiyle orta derecede yaş, meslek ve gelir durumu ile oldukça düşük düzeyde etki değerinin olduğu bulunmuştur.
Dindar Bireylerin İslami Finans Prensipleri, İslami Finans Ürünlerine İlişkin Bilgi Düzeyi ve İlişkisi Üzerine Bir Araştırma
Keywords: Monetary-Banking; Para-Bankacılık; Sociology of Religion; Din Sosyolojisi; Industrial Marketing; Endüstriyel Pazarlama